Synthesis and SAR of 2, 3‐Dihydro‐1‐benzofuran‐4‐carboxylates: Potent Salicylic Acid‐Based Lead Structures against Plant Stress. Issue 14 (17th March 2022) - Bojack, Guido; Brown, Ronald W.; Dittgen, Jan; Heinemann, Ines; Helmke, Hendrik; Hills, Martin J.; Hohmann, Sabine; Holstein, Philipp M.; Schmutzler, Dirk; Frackenpohl, Jens
Abstract: New 2, 3‐dihydro‐1‐benzofuran‐4‐carboxylic acid derivatives have been identified as potent lead structures against drought and cold stress in crops starting from the synthetic exploration of stabilized analogs of the natural product lunularic acid. An optimized Lewis‐acid mediated cyclization gave a short and efficient access to the envisaged 2, 3‐dihydro‐1‐benzofuran‐4‐carboxylates. Enantioselective approaches were investigated to assess the potential impact of the chiral center on in vivo activity. Whilst 2, 3‐dihydro‐1‐benzofuran‐4‐carboxamides and 2, 3‐dihydro‐1‐benzofuran‐4‐carboxylates carrying phenyl substituents with electron‐withdrawing groups exhibited only low to moderate in vivo activity, the corresponding 2, 3‐dihydro‐1‐benzofuran‐4‐carboxylates carrying optimized electron‐donating substituents in the phenyl moiety revealed strong in vivo activity, both against drought stress in several broad‐acre crops, as well as against cold stress in corn. Remarkably, several 2, 3‐dihydro‐1‐benzofuran‐4‐carboxylates showed stronger efficacy than the internal standards used in our in vivo SAR study. Abstract : In the agrochemical in vivo SAR‐study described in this work, it is outlined how a lead structure that had emerged from rational design inspired by natural products from liverworts and hydrangea has been identified, explored and optimized. In the course of the in‐depth SAR study, several new potent 2, 3‐dihydro‐1‐benzofuran‐4‐carboxylates have been identified that show improved in vivo efficacy against drought and cold stress in broad‐acre crops such as corn, wheat and canola compared with the initial lead structure.